A compact ultra wideband antenna with band-notched design - Jalil Y.E.; Chakrabarty C.K.; Kasi B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antenna grounds; Bandpass filters; Bandwidth; Communication channels (information theory); Directional patterns (antenna); Frequency bands; Microstrip antennas; Microwave antennas; Radio transmission; Slot antennas; Transient analysis; frequency-notched; H-shaped slots; Narrowband systems; Signal transmission; Spectrum overlapping; Ultra-wideband antennas; UWB impulse radio; Wideband systems; Ultra-wideband (UWB)